Grain-size analysis obtained from sediment core BT02 (Eiderstedt peninsula; south-eastern North Sea) - Nina Lenz; Sebastian Lindhorst (PANGAEA, 2021)
Core BT02 originates from a reinstated, former managed marsh (Eiderstedt peninsula). The marsh in Eiderstedt is exposed to storm waves from the open North Sea. Grain-size data were used to determine and quantify multiple sedimentary processes by the application of end-member modelling.
In: Lenz, N; Lindhorst, S (2021): Grainsize analysis and radionuclide measurements (210Pb, 137Cs, 226Ra) obtained from sediment cores RD04 (island of Sylt), BT02 and BT03 (Eiderstedt peninsula; south-eastern North Sea) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.933869